Computer and electronic duster spray inhalation (huffing) injuries managed at emergency departments. (3rd March 2020) - Forrester, Mathias B.
ABSTRACT: Background : Computer and electronic duster sprays contain halogenated hydrocarbon gases. Intentional inhalation of computer and electronic duster sprays to induce intoxication, also known as huffing, may cause serious adverse effects and even death. Objectives : Describe computer and electronic duster spray inhalation-related injuries managed at United States (US) emergency departments (EDs). Methods : Data were obtained from the National Electronic Injury Surveillance System (NEISS), a database of consumer product-related injuries collected from the EDs of approximately 100 hospitals in the US. Cases were computer and electronic duster spray inhalation-related injuries included in NEISS during 2001–2017. The distribution by selected variables was determined for the resulting cases as well as a weighted estimate. Results : A total of 320 computer and electronic duster spray inhalation-related injuries were identified, resulting in a national estimate of 14, 715 (95% confidence interval 11, 120–18, 311) such injuries. The annual estimated number of injuries remained low during 2001–2008 then increased during 2008–2017. Of the estimated injury patients, 3.2% were aged 6–12 years, 20.3% 13–19 years, and 76.5% 20–59 years; 65.4% of the patients were male. The disposition of the patient was 71.4% treated and examined and released, 6.9% treated and transferred, 11.6% treated and admitted or hospitalized, 0.7% held for observation, and 8.7% left without being seen. Conclusion : This study suggests that computer and electronic duster spray inhalation (huffing) may be an increasing issue of which hospital EDs and other clinicians should be aware. The pattern of injuries observed may be useful for targeting education, prevention and management activities.